2019
DOI: 10.1186/s12883-019-1324-4
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing optic neuritis and meningoencephalitis in a child: case report of delayed diagnosis of MOG-IgG syndrome

Abstract: Background Recurrent optic neuritis (ON) was previously thought to be associated with multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD). Meningoencephalitis has recently been suggested to be a clinical finding typical of myelin oligodendrocyte glycoprotein (MOG) encephalomyelitis. We report a Chinese patient with recurrent ON at disease initiation, who had a delayed diagnosis of MOG-IgG syndrome, until recurrent meningoencephalitis appeared and serum MOG-IgG was detected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…15 Two further single cases were recently published, describing children with symptoms suggestive of encephalitis associated with MOG abs but with MRI features more reminiscent of ADEM underscoring the need for precise terminology and diagnostic standards for children with MOG-SD. 25,26 Recently, Armangue et al showed that the spectrum of MOG-SD is wider than previously reported including children with encephalitis. 27 In their large cohort of children with ADS and encephalitis, they found that 22/296 children with definite or possible AE harbored MOG abs.…”
Section: Discussionmentioning
confidence: 97%
“…15 Two further single cases were recently published, describing children with symptoms suggestive of encephalitis associated with MOG abs but with MRI features more reminiscent of ADEM underscoring the need for precise terminology and diagnostic standards for children with MOG-SD. 25,26 Recently, Armangue et al showed that the spectrum of MOG-SD is wider than previously reported including children with encephalitis. 27 In their large cohort of children with ADS and encephalitis, they found that 22/296 children with definite or possible AE harbored MOG abs.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, 7 cases of MOG-ADassociated meningitis, which were described to have fever, nausea, and nuchal rigidity, have been reported including our case (Table) (10)(11)(12)(13)(14)(15)(16). The mean age of these patients was 24.4 years (range: 3-55); four of these patients were male.…”
Section: Discussionmentioning
confidence: 76%